Dietary Amylose/Amylopectin Ratio Modulates Cecal Microbiota and Metabolites in Weaned Goats - Gebeyew, Kefyalew; Chen, Kai; Wassie, Teketay; Azad, Md. Abul Kalam; He, Jianhua; Jiang, Weimin; Song, Wu; He, Zhixiong; Tan, Zhiliang (Frontiers in Nutrition, 2021)
Increasing the ratio of amylose in the diet can increase the quantity of starch that flows to the large intestine for microbial fermentation. This leads to the alteration of microbiota and metabolite of the hindgut, where the underlying mechanism is not clearly understood. The present study used a combination of 16S rRNA MiSeq sequencing technology and metabolomics technique to reveal the effects of increasing ratios of amylose/amylopectin on cecal mucosa-and digesta-associated microbiota and their metabolites in weaned goats. Twenty-seven Xiangdong black female goats with average body weights (9.00 ± 1.12 kg) were used in this study. The goats were randomly allocated to one of three diets containing starch with 0% amylose corn (T1), 50% high amylose corn (T2), and 100% high amylose corn (T3) for 35 days. Results showed that cecal valerate concentration was higher (P < 0.05) in the T2 group than those in the T1 and T3 groups. The concentrations of cecal tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 were decreased (P < 0.05) while IL-10 and interferon-α (IFN-α) were increased (P < 0.05) in the T2 group when compared with T1 or T3 groups. At the phylum level, the proportion of mucosa-associated Spirochaetes was increased (P < 0.05), while Proteobacteria was deceased by feeding high amylose ratios (P < 0.05). The abundance of Verrucomicrobia was decreased (P < 0.05) in the T3 group compared with the T1 and T2 groups. The abundance of digesta-associated Firmicutes was increased (P < 0.05) while Verrucomicrobia and Tenericutes were deceased (P < 0.05) with the increment of amylose/amylopectin ratios. The LEfSe analysis showed that a diet with 50% high amylose enriched the abundance of beneficial bacteria such as Faecalibacterium and Lactobacillus in the digesta and Akkermansia in the mucosa compared with the T1 diet. The metabolomics results revealed that feeding a diet containing 50% high amylose decreases the concentration of fatty acyls-related metabolites, including dodecanedioic acid, heptadecanoic acid, and stearidonic acid ethyl ester compared with the T1 diet. The results suggested that a diet consisting of 50% high amylose could maintain a better cecal environment and host immune function.